Oral epithelial cells and their interactions with HIV‐1. (16th February 2016) - Moyes, DL; Islam, A; Kohli, A; Naglik, JR
Abstract : As the AIDS pandemic has continued, our understanding of the events that occur during the entry and infection of conventional, susceptible cells has increased dramatically, leading to the development of control therapies for HIV‐infected individuals. However, an ongoing hole in our understanding is how HIV crosses the mucosal barriers to gain access to permissive cells, despite how important this information would be in developing successful vaccines and other preventative measures such as topical anti‐HIV microbicides. In particular, our knowledge of the role that epithelial cells of the mucosal surfaces play in infection – both during early phases and throughout the life of an infected individual, is currently hazy at best. However, several studies in recent years suggest that HIV can bind to and traverse these mucosal epithelial cells, providing a reservoir of infection that can subsequently infect underlying permissive cells. Despite this interaction with epithelial cells, evidence suggests HIV‐1 does not productively infect these cells, although they are capable of transferring surface‐bound and transcytosed virus to other, permissive cells. Further, there appear to be key differences between adult and infant epithelial cells in the degree to which HIV can transcytose and infect the epithelium. Thus, it is clear that, whilst not primary targets for infection and virus replication, epithelial cells play an important role in the infection cycle and improving our understanding of their interactions with HIV could potentially provide key insights necessary to develop effective preventative therapies.